33Cl Spectroscopic Factors via the 32S(3He, d)33Cl One-Proton Transfer Reaction. (1st March 2023) - Cinausero, M; Dell'Aquila, D; Lombardo, I; Vigilante, M; Barlini, S; Bolzonella, R; Bruno, M; Buccola, A; Cartuan, S; Casini, G; Cicerchia, M; D'Andrea, M; et al.
Abstract: The structure of light-to-medium mass nuclei is crucial to understand exotic phenomena in nuclear structure, including the appearance of molecular effects in light nuclei and their impact in nuclear astrophysics. In this paper, a new experiment to probe one-proton spectroscopic factors of bound and unbound states in the sd-nucleus 33 Cl is discussed. The experiment exploits the reaction 32 S( 3 He, d) 33 Cl * at 9.68 MeV bombarding energy. This reaction is suitable to probe the single-particle structure of 33 Cl states with respect to the population of 1 d 3/2, 1 f 7/2 and 2 p 3/2 shells. Crucial aspects of the investigation are the use of an enriched, high-purity, 32 S target and a new generation hodoscope with improved angular resolution, allowing to obtain high-precision angular distribution of the differential cross section in a broad angular range. Results are interpreted by means of finite-range DWBA and coupled-channel calculations.